Simulation Investigation of Solar PV Rooftop Design at Faculty of Engineering-Universiti Malaysia Sarawak Building, Malaysia - Yanuar Zulardiansyah, Arief; Anatassia Lampai, Abut; Naemah, Mubarakah; Yulianta, Siregar; Hamzah, Eteruddin; Hendri, Masdi (2024)
Renewable energy is increasingly employed as a substitute for conventional energy due to its detrimental environmental effects. Various forms of renewable energy, such as solar, wind, biomass, and geothermal energy, are commonly utilized. Given Malaysia's consistently hot and humid climate, solar energy has gained significant traction in the country. The recent rise in solar farm installations and rooftop solar systems is particularly notable. Rooftop solar systems, particularly suitable for urban settings due to their installation on building rooftops without requiring additional space, were the focus of a project aimed at designing a rooftop solar system for the Faculty of Engineering buildings at UNIMAS. The design and evaluation of a grid-connected PV system were conducted using PVSyst 7.2 software, with climate data collected through Meteonorm 8.0 Power demand, determined with Fluke 435 power analyzer, guided the sizing of the PV system. The simulation involved varying types of solar panels to identify the most efficient for the PV system's performance. Inverter specifications remained consistent throughout the simulation. Results revealed that, to fulfill the building's power demand, a 105kW PV system with 525 Si-Mono 200Wp 24V panels and nine 9.0kW inverters exhibited the highest Performance Ratio, leading to the selection of this design for the project.